OCORA OCR 43. Musique Centrafricaine. Charles Duvelle. LP 12". (International Library of African Music, 1969)
The items featured include music from ten different tribes within the Republique Centrafricaine, mostly from the regions around the capital Bangui. The descriptive matter is printed in both French and English. The quality of this recording as well as its presentation is well up to Ocora standards. The music is interesting and the photographs of the performers admirably illustrate the text.
Keywords: African Music